Роль языковых средств при описании польско-российских отношений в текстах, посвященных теме Катыни (на материале „Газеты Выборча” за период 1989–1999 гг.) - Lukianov, Dmitrii (Studia Rossica Posnaniensia, 2022)
In order to form a certain image, media employ various linguistic means, such as metaphors, comparative structures, etc. Based on the material from “Gazeta Wyborcza” concerning the topic of the Katyn massacre, the present study attempts to reconstruct the image of Polish-Russian relations and decide what role the linguistic means used in the articles play in creating the discussed phenomenon. As a result the author concludes that there are two points of view about Russia presented in “Gazeta Wyborcza”. On the one hand, Russia is a criminal country and a debtor that cannot fulfil its obligations. On the other hand, Russia is a state that is open for cooperation and capable of helping. There are also two different points of view about the Polish-Russian relationships. As stated by some experts, Polish-Russian relations in the analyzed period are characterized as negative. According to the other opinions (prior to the 2022 war), these relations are getting better and perhaps will continue to improve.